Application of a novel amplicon-based sequencing approach reveals the diversity of the Bacillus cereus group in stored raw and pasteurized milk. (August 2019) - Porcellato, Davide; Aspholm, Marina; Skeie, Siv Borghild; Mellegård, Hilde
Abstract: Members of the Bacillus cereus sensu lato ( B. cereus group) are spore-forming organisms commonly associated with spoilage of milk and dairy products. Previous studies have shown, by using 16S marker gene sequencing, that the genus Bacillus is part of the core microbiota of raw bovine milk and that some members of this genus are able to grow during sub-optimal storage (8 °C) of pasteurized consumption milk. Here, the composition of this genus in pasteurized consumption milk samples, collected from two dairies, over a one-year period and stored at 4 or 8 °C up to the end of shelf life is uncovered. Our results show that the B. cereus group is the dominant Bacillus group in stored consumption milk. By applying a new marker gene sequencing approach, several dominating phylogenetic clusters were identified within the B. cereus group populations from the milk samples. There was a higher phylogenetic diversity among bacteria from milk stored at 8 °C compared to milk stored at 4 °C. Sampling period and the dairy the samples were collected from, also significantly influenced the diversity, which shows that the B. cereus group population in consumption milk is heterogeneous and subjected to temporal and spatial changes. The new approach applied in this study will facilitate the identification of isolates within the B. cereus group, of which some are potential spoilage bacteria and pathogenic contaminants of milk and dairy products. Highlights: A new high throughput sequencing approach was developed to target the Bacillus cereus group. Bovine milk contained a complex B. cereus group population dominated by diverse sequence groups of psychrotolerant strains. The dynamics of the B. cereus group population in milk was influenced by storage temperature, sampling period and dairy.